1999
DOI: 10.1016/s0092-8674(00)81522-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Eukaryotic Zinc-Binding Proteins Is Required for Disease Resistance Signaling in Barley and Development in C. elegans

Abstract: Barley Rar1 is a convergence point in the signaling of resistance to powdery mildew, triggered by multiple race-specific resistance (R) genes. Rar1 is shown to function upstream of H2O2 accumulation in attacked host cells, which precedes localized host cell death. We isolated Rar1 by map-based cloning. The sequence of the deduced 25.5 kDa protein reveals two copies of a 60-amino acid domain, CHORD, conserved in tandem organization in protozoa, plants, and metazoa. CHORD defines a novel eukaryotic Zn2+-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
305
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(310 citation statements)
references
References 37 publications
3
305
1
1
Order By: Relevance
“…The plant SGT1 (Suppressor of G2 allele of skp1) gene was first isolated independently by two laboratories; one in the searching for interacting proteins for the key signaling component of multiple R-gene-mediated resistance, RAR1 [12], and the other in the screening for the genes essential for R gene RPP5-mediated disease resistance, respectively [92,93]. Studies from several groups indicated that SGT1 is required by a diverse range of R genes from different plant species in response to a variety of pathogens [61,[92][93][94][95].…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 99%
“…The plant SGT1 (Suppressor of G2 allele of skp1) gene was first isolated independently by two laboratories; one in the searching for interacting proteins for the key signaling component of multiple R-gene-mediated resistance, RAR1 [12], and the other in the screening for the genes essential for R gene RPP5-mediated disease resistance, respectively [92,93]. Studies from several groups indicated that SGT1 is required by a diverse range of R genes from different plant species in response to a variety of pathogens [61,[92][93][94][95].…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 99%
“…The function of these proteins in disease resistance responses have been extensively investigated previously using mutant analyses Chandra-Shekara et al, 2004;Hubert el al., 2003;Lu et al, 2003;Shirasu et al, 1999;Takahashi et al, 2003) and by virus induced gene silencing (VIGS) analyses in several plant species (Bhattarai et al, 2007;de la Fuente van Bentem et al, 2005;Leister et al, 2005;Liu et al, 2004;Scofield et al, 2005). The data from these studies revealed differing specificities for these proteins in diverse NB-LRR-mediated resistance responses.…”
Section: Discussionmentioning
confidence: 99%
“…http://molcells.org Established in 1990 RAR1, encoding a eukaryotic zinc-binding protein, was originally identified in barley due to its requirement for the Mla12-mediated resistance to powdery mildew (Shirasu et al, 1999). It was later found to be essential for Mla6, but not Mla1, resistance (Azevedo et al, 2002).…”
Section: Molecules and Cellsmentioning
confidence: 99%
“…For example, the barley Rar1 and Rar2 genes have partial resistance phenotypes in cultivars carrying several powdery mildew R genes (Shirasu et al 1999). The partial loss of resistance may indicate that genes required for disease resistance are redundant or part of branched pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, these genes were each shown to be required to transduce the signal of multiple R genes (Century et al 1997;Innes 1998). The cloned barley gene, Rar1, is required for multiple R gene-mediated resistance to powdery mildew pathways (Shirasu et al 1999).…”
Section: Introductionmentioning
confidence: 99%